A successful heart and liver transplantation requiring intraoperative extracorporeal membrane oxygenation for primary cardiac allograft dysfunction in a patient with Fontan failure. Issue 6 (25th April 2020) - Siddiqi, Umar A.; Hibino, Narutoshi; Combs, Pamela S.; Baker, Talia; Song, Tae; Kim, Gene; Jeevanandam, Valluvan
Abstract: We report a case of successful heart and liver transplantation requiring intraoperative extracorporeal membrane oxygenation (ECMO) for primary cardiac allograft dysfunction in a patient with Fontan failure. A successful outcome for both the heart and the liver can be achieved with the timely management of ECMO support. In describing our experiences treating a Fontan patient requiring multiorgan transplantation, we have shown that challenging cases such as this one can have successful outcomes if multidisciplinary collaborations and proper treatment strategies are utilized at the optimal timing, along with family support and patient cooperation.